2000
DOI: 10.1001/archsurg.135.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Outcome for Older Burn Patients

Abstract: Background: Physicians will be increasingly responsible for an aging society whose members demonstrate a notable striving for independence. Hypothesis: With standard treatment of burns, older patients will have a survival rate of more than 70%, with at least 60% of patients becoming fully functional 6 months after hospital discharge. Methods: A 7-year retrospective medical record review of burn unit patients was performed, and 221 (11%) of 1957 patients who were at least 59 years old were identified. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 18 publications
2
17
0
4
Order By: Relevance
“…There have so far been a few reports showing that patients with impaired movement due to cerebrovascular disease or Parkinson syndrome tend to suffer severe burn injuries and have worse outcomes (Raff et al 1996;Germann et al 1997;McGill et al 2000). Our results show that an impaired mobility results in a longer exposure to the burning agent, thereby leading to severe burn injuries and a poor prognosis.…”
Section: Discussionsupporting
confidence: 46%
“…There have so far been a few reports showing that patients with impaired movement due to cerebrovascular disease or Parkinson syndrome tend to suffer severe burn injuries and have worse outcomes (Raff et al 1996;Germann et al 1997;McGill et al 2000). Our results show that an impaired mobility results in a longer exposure to the burning agent, thereby leading to severe burn injuries and a poor prognosis.…”
Section: Discussionsupporting
confidence: 46%
“…Inhalation injury of the lung in adults is usually proportional to the depth and extent of body surface area burned (252,279,342,440). Children have a lower rate of inhalation injury because of the prominence of scald injury in this group (200,320).…”
Section: Inhalation Injurymentioning
confidence: 99%
“…A recent review of adult patients admitted to a burn center over a 7-year period showed that 221 of 1,557 (11%) were Ͼ59 years of age and a higher proportion were women (279). Most elderly burn patients had one or more existing medical conditions and impaired judgment and/or mobility.…”
Section: Impact Of Patient Demographics and Burn Severitymentioning
confidence: 99%
“…On the other hand, in elderly patients who are not good to accommodate to stress and presence of coexistent diseases are effecting burns treatment and treatment results in a negative way [11]. In studies conducted, burns are noted to be at 4 th place in geriatric patients' death due to injuries [12].…”
Section: Discussionmentioning
confidence: 99%